2011
DOI: 10.3324/haematol.2011.042945
|View full text |Cite
|
Sign up to set email alerts
|

ADAMTS13 activity and antigen during therapy and follow-up of patients with idiopathic thrombotic thrombocytopenic purpura: correlation with clinical outcome

Abstract: BackgroundThe assay for ADAMTS13 activity helps clinicians to confirm the clinical diagnosis of idiopathic thrombotic thrombocytopenic purpura. The clinical value of testing for the antigen level of ADAMTS13 protein is, however, less clear. Design and MethodsIn this study, both ADAMTS13 antigen and activity levels were measured in 835 sequential samples from 40 consecutive patients who were followed for an average of 29 months throughout the course of acute episode plasma exchange treatment and clinical remiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
29
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 27 publications
6
29
1
4
Order By: Relevance
“…By contrast, previously employed methods detected immune complexes only indirectly by measuring ADAMTS13:Ag or ADAMTS13:Ac in IgG-depleted plasma 20,21 or by a poorly reported direct detection of the IgG antibody portion of the ADAMTS13-immune complexes using a commercial kit to quantify ADAMTS13:Ag levels in a limited number of patients. 22 The most relevant finding of our study was the detection of IgG-immune complexes in 93% of patients in remission, independently of the duration of the remission. This strongly indicates that ADAMTS13-specific immune complexes circulate in patients with acquired TTP patients throughout the entire course of the disease and many years after clinical remission.…”
Section: A B Cmentioning
confidence: 56%
See 1 more Smart Citation
“…By contrast, previously employed methods detected immune complexes only indirectly by measuring ADAMTS13:Ag or ADAMTS13:Ac in IgG-depleted plasma 20,21 or by a poorly reported direct detection of the IgG antibody portion of the ADAMTS13-immune complexes using a commercial kit to quantify ADAMTS13:Ag levels in a limited number of patients. 22 The most relevant finding of our study was the detection of IgG-immune complexes in 93% of patients in remission, independently of the duration of the remission. This strongly indicates that ADAMTS13-specific immune complexes circulate in patients with acquired TTP patients throughout the entire course of the disease and many years after clinical remission.…”
Section: A B Cmentioning
confidence: 56%
“…17,18 With the isolation of inhibiting IgG antibodies against ADAMTS13 from plasma of TTP patients, the presence of ADAMTS13-specific immune complexes became plausible, 19 with the following observations supporting their existence: (i) removal of anti-ADAMTS13 IgG antibodies also removed measurable residual ADAMTS13 antigen; 20 (ii) residual ADAMTS13 activity was no longer measurable after plasma IgG depletion; 21 and (iii) human IgG bound to ADAMTS13 were identified by adaptation of a commercial ADAMTS13 antigen enzymelinked immunosorbent assay (ELISA). 22 Recently, we demonstrated the presence of ADAMTS13-specific immune complexes in a patient with refractory acquired TTP using a co-immunoprecipitation technique. 23 This observation prompted us to investigate the prevalence of ADAMTS13-specific immune complexes in a large cohort of patients with acquired TTP during the acute phase and in remission.…”
Section: Introductionmentioning
confidence: 99%
“…20 The role of ADAMTS13 antigen levels in TTP is even less well characterized; however, emerging evidence suggests depletion of the ADAMTS13 antigen may be the dominant pathologic mechanism 21 and its levels a significant prognostic indicator. 22 Using the UK TTP registry, we have investigated whether the presenting levels of anti-ADAMTS13 IgG antibody and ADAMTS13 antigen had any effect on the mortality of patients presenting with acute TTP. As other studies have suggested, with a raised cardiac troponin level 13,14 and neurological involvement 10,12 as poor prognostic markers, these were also included in our investigation of risk factors for mortality in acute TTP.…”
Section: Introductionmentioning
confidence: 99%
“…However, the extent to which these antibodies circulate in plasma in their free form or as a complex with ADAMTS13 and how this proportion changes over time is unclear. We and others have recently reported indirect detection by an ADAMTS13 antigen (ADAMTS13:Ag) ELISA of IgG ADAMTS13‐specific immune complexes (ICs) in plasma from patients with acquired TTP [5,6]. In the present study we used another more direct method for detecting ICs and compared the levels of free anti‐ADAMTS13 antibodies, ADAMTS13:Ag, ADAMTS13 activity (ADAMTS13:Ac) and inhibitor with those of ICs.…”
mentioning
confidence: 98%